Constraining cosmic-ray acceleration in the magnetospheric gaps of Sgr A* - Katsoulakos, Grigorios; Rieger, Frank M.; Reville, Brian (The astrophysical journal. Part 2, Letters, 2020)
Sagittarius A* (Sgr A*) is a potential very high energy (VHE) γ-ray and cosmic-ray source. We examine limits to gap-type particle acceleration in the magnetosphere of Sgr A*, showing that in the current phase of activity proton acceleration to PeV energies is possible, with injection powers into the environment usually limited to several 1036 erg s−1. Compton upscattering of ambient soft photons by gap-accelerated electrons could yield TeV emission compatible with the detected VHE point source. We explore the dependency of the results on changes in the accretion rate showing that higher stages in the past are unlikely to increase the power output unless the inner accretion flows itself changed its configuration.